Olive: Native of Mediterranean region and Health benefits - Omar, Syed Haris (Pharmacognosy Reviews)
The Olive tree (Olea europaea) is native to the Mediterranean region, tropical & central Asia and various parts of Africa. It is an integral ingredient of the diet in the form of whole fruit or oil in the countries surrounding the Mediterranean Sea. The constituents of olive categorized into major and minor components. Major component of olive oil consist of oleic acid (Triglycerides) and a large number of minor components includes phenolic constituents, squalene, α-tocopherol and sterols having great importance and beneficial to human health. The main phenolics include hydroxytyrosol, tyrosol, and oleuropein, which occur in highest levels in virgin olive oil and have demonstrated antioxidant activity. Many studies have been conducted to prove its potential through oil, whole fruit and leaf extract as cardiovascular disorders and anti-oxidant, gastroprotective effect, osteoprotective effect, endocrine effect, immunomodulatory effect, anti-cancer, anti-viral and anti-microbial effects.
Keywords: Olive; Mediterranean diet; cardiovascular disorder; anti-cancer; antimicrobial